Morphology biomechanics of track and field competitors - Erdmann, W. S. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The paper presents description of relationship between morphological quantities of sportsperson`s body build and mechanics of movement. Morphology biomechanics, i.e. structure, biomaterials, construction, geometry, inertia was described. Main groups of track and field disciplines (race walking, running, jumping, throwing) were presented and their relationship with competitor`s mechanical body build.